The importance of models for teaching Physics: focusing on Archimedes' principle in high school textbooks - Salmon Landi Júnior; Nyuara Araújo da Silva Mesquita; Wellington Pereira de Queirós (Amazônia)
This study sought to identify and discuss the explanatory models for approaching Archimedes' principle in Natural Sciences textbooks approved by the Programa Nacional do Livro e do Material Didático 2021. In addition, an explanatory model that can be implemented in Physics classes, based on the relationship between experimentation and mathematical and theoretical elements was proposed. Regarding the analysis of the textbooks, it was observed that the presentation of Archimedes' principle, in most cases, was disconnected from the theoretical foundation and supported by mathematical equations that are not properly explained. In turn, the explanatory model proposed here seeks to elucidate conceptual and mathematical aspects, contributing to a more reflective approach in High School Physics classes.